Experimental and thermodynamic description of ternary Bi-Cu-Ga system - Minić D.; Du Y.; Premović M.; Manasijević D.; Talijan N.; Milisavljević D.; Marković A.; Đorđević A.; Tomović M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Phase diagram of the Bi-Cu-Ga ternary system has been investigated experimentally with 27 alloys and analytically by using a Calphad method. Thirteen annealed alloys at 200°C were investigated by using scanning electron microscopy (SEM) with energy dispersive spectrometry (EDS), and X-ray powder diffraction (XRD) methods. Temperatures of phase transformation were determined with 14 alloys which are lying along three vertical sections Bi-Cu0.5Ga0.5, Cu-Bi0.5Ga0.5 and Ga-Bi0.5Cu0.5 by using differential thermal analysis (DTA). Based on the experimental result and by using Calphad method, ternary phase diagrams were constructed with a new description of liquidus phase. Calculated phase diagram and experimentally obtained results are in good agreement. Liquidus projection and invariant reaction were calculated by using new thermodynamic parameters for liquidus phase. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. OI172037]